analysis of radon and radium content in springs of ekaterinburg city and its settlements - Vladimir S. Semenishchev; Anna V. Voronina; Lyubov A. Tomashova; Yulia I. Nasonova (Водное хозяйство России: проблемы, технологии, управление)
Despite development of central water supply systems, springs still remain to be important sources of drinking water. In this work, the study of water quality in springs of Yekaterinburg city and its settlements was performed with the attention to radiological factor. Activity concentrations of radium-226 were determined in water of 20 springs.